Interpreting the New Testament essays on methods and issues - Black, David Alan, 1952-; Dockery, David S. (Nashville, TN Broadman and Holman, 2001)
Includes bibliographical references and indexes.
Originally published : New Testament criticism and interpretation, 1991, which see also.
Keywords: Bible. N.T. -- criticism, interpretation, etc; Bible. N.T. -- hermeneutics